1999
DOI: 10.1159/000011960
|View full text |Cite
|
Sign up to set email alerts
|

Serial Transplants of DMBA-Induced Mammary Tumors in Fischer Rats as a Model System for Human Breast Cancer

Abstract: Previous studies on human breast cancer patients showed a decline in circulating melatonin levels corresponding to primary tumor growth and an increase when relapse occurred. The aim of the current investigation was to study in an experimental model possible mechanisms involved. Inbred female F344 Fischer rats were used for serial passages derived from a chemically induced mammary adenocarcinoma. Animals with slow-growing carcinosarcomas at passage 2 showed a significant elevation of nocturnal urinary melatoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…However, when high doses of DMBA were used, there was no significant difference between pinealectomized or sham-operated animals in the incidence of mammary neoplasms [5]. Transplanted DMBA-induced mammary tumors grew more slowly after melatonin treatment as compared to control rats that did not receive melatonin [9].…”
mentioning
confidence: 96%
“…However, when high doses of DMBA were used, there was no significant difference between pinealectomized or sham-operated animals in the incidence of mammary neoplasms [5]. Transplanted DMBA-induced mammary tumors grew more slowly after melatonin treatment as compared to control rats that did not receive melatonin [9].…”
mentioning
confidence: 96%
“…Investigating any circardian rhythm in MEL secretion may help to confirm or refute this hypothesis. In patients with many types of breast, prostate, colon or uterus cancer, a decrease in night‐time MEL secretion has been reported (4, 8, 16). Bartsch et al .…”
Section: Discussionmentioning
confidence: 99%
“…Bartsch et al . (8, 16) reported that a growing tumour could modulate MEL biosynthesis. An initial increase is followed by a decrease in MEL biosynthesis, which can indicate neoplastic disease dissemination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on this results, the researcher assume that cancer induction by carcinogen compounds DMBA and Estradiol for 2 months has not resulted in excessive inflammatory reactions to cause cachexia syndrome. In rats model, DMBA can cause cachexia after 195 days of administration, while in 1 month administration of DMBA was not enough to promote cachexia syndrome [42,43]. TNF-α is cytokines that play major role to cause cachexia syndrom, and the increasing number of TNF-α can be considered as cachexia symtomps, because TNF-α responsible to degradation of myofibrillar and soleus muscle proteins [44].…”
Section: Issnmentioning
confidence: 99%